2019
DOI: 10.1186/s41936-019-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

The potential roles of aluminum chloride and sodium fluoride on the neurotoxicity of the cerebral cortex, hippocampus, and hypothalamus of male rat offspring

Abstract: Background: This study highlights the potential toxic effects of aluminum chloride and sodium fluoride (NaF), given to pregnant female rats, on the development of the brain neurotransmission systems in their offspring. Pregnant female rats received a daily dose of NaF (0.15 g/L) or AlCl 3 (0.5 g/L) in the drinking deionized water, either separately or in combination with each other, starting from the 6th day of gestation till the end of the breastfeeding period. After weaning, the male offspring were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Reduced levels of neurotransmitters belonging to the biogenic amine family in the brain is connected with a decline in memory in aging people [35]. In our study, AlCl 3 significantly reduced noradrenaline, dopamine and serotonin levels in rat brains, in agreement with Kinawy et al [36] and Foster et al [37]. The treatment of rats with the extract significantly increased all monoamine levels.…”
Section: Discussionsupporting
confidence: 91%
“…Reduced levels of neurotransmitters belonging to the biogenic amine family in the brain is connected with a decline in memory in aging people [35]. In our study, AlCl 3 significantly reduced noradrenaline, dopamine and serotonin levels in rat brains, in agreement with Kinawy et al [36] and Foster et al [37]. The treatment of rats with the extract significantly increased all monoamine levels.…”
Section: Discussionsupporting
confidence: 91%
“…Al can act as a neurotoxin that has a wide efect on multiple organs [2]. It has been observed that aluminum easily enters the brain and accumulates in it, and the highest amount is seen in younger rats, indicating the importance of accumulating this metal in the early life of the animal [3]. Some of the diseases that have been proven to be associated with aluminum are Parkinson's disease, dementia, and Alzheimer's [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Existing literature have been associated with fluoride exposure to the cause of neurological motor and cognitive deficit in both matured and growing brains. 19,20 Although, there has been lack of data to support the effect of fluoride on autonomic functions and possible therapeutic approaches. Therefore, the present study was initiated to evaluate the impact of sodium fluoride through drinking water on the activities of the pons.…”
Section: Introductionmentioning
confidence: 99%